Risk Assessment of Cadmium, Lead, and Mercury on Human Health in Relation to the Consumption of Farmed Sea Bass in Italy: A Meta-Analytical Approach - Di Bella, Calogero; Calagna, Antonino; Cammilleri, Gaetano; Schembri, Pietro; Lo Monaco, Daniela; Ciprì, Valentina; Battaglia, Luisa; Barbera, Giuseppe; Ferrantelli, Vincenzo; Sadok, Saloua; Tliba, Ines; Lo Dico, Gianluigi Maria; et al. (Frontiers in Marine Science, 2021)
A risk assessment, related to the consumption of farmed sea bass, was carried out by meta-analysis, taking into account the concentration of trace metals (Cd, Pb, Hg) reported in the literature, the estimated weekly intake (EWI), the provisional tolerable weekly intake (PTWI), and the target hazard quotient (THQ). The concentrations of Cd, Pb, and Hg in farmed sea bass marketed in Sicily (Southern Italy) were also assessed by inductively coupled plasma mass spectrometry (ICP-MS) and atomic absorption spectroscopy (AAS) to have screening data for the comparison with literature results. In any case, the results obtained by meta-analysis and by screening were lower than the pre-established legal limits for each metal. The meta-analysis results showed very low levels of Cd (0.031 μg g–1 w.w.), Pb (0.110 μg g–1 w.w.), and Hg (0.023 μg g–1 w.w.). The EWI estimation confirmed safety limits for human health (0.004, 0.015, and 0.003 μg kg–1 for Cd, Pb, and Hg, respectively). Even the THQ demonstrated that farmed sea bass represent a secure food for humans (0.0006, 0.0005, and 0.0048 for Cd, Pb, and Hg, respectively). The comparison with our screening data showed a significant difference only for the Pb levels (p < 0.05). The results obtained were compared with the same indexes relative to other food types (meat, cereals, vegetables, etc.). The EWI and THQ calculated were always lower than same indexes relative to other food types considered.